2007
DOI: 10.1182/blood-2007-01-071043
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory autoantibodies to PDGF receptor in patients with extensive chronic graft-versus-host disease

Abstract: Extensive chronic graft-versus-host disease (ecGVHD) is characterized by fibrosis similar to that of patients with systemic sclerosis (scleroderma). Since stimulatory autoantibodies against the platelet-derived growth factor (PDGF) receptor (PDGFR) have been found in patients with scleroderma and are responsible for the activation of skin fibroblasts, we tested the hypothesis that these autoantibodies are also present in patients affected by ecGVHD. Serum from 39 patients subjected to allogeneic stem cell tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
155
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(163 citation statements)
references
References 14 publications
1
155
3
1
Order By: Relevance
“…Their actions are mainly by reducing the amount of fibrosis in conjunction by counteracting effects of TGFβ and platelet-derived growth factor (PDGF). These findings are supported by the presence of agonistic antibodies found in cGVHD to the receptors of these cytokines [133]. In a phase I/II trial, imatinib at 100 mg/ day was used to treat 19 patients, both adult and pediatric, who had refractory sclerotic cGVHD of skin, gastrointestinal tract, or cGVHD of lungs.…”
Section: Imatinibmentioning
confidence: 92%
“…Their actions are mainly by reducing the amount of fibrosis in conjunction by counteracting effects of TGFβ and platelet-derived growth factor (PDGF). These findings are supported by the presence of agonistic antibodies found in cGVHD to the receptors of these cytokines [133]. In a phase I/II trial, imatinib at 100 mg/ day was used to treat 19 patients, both adult and pediatric, who had refractory sclerotic cGVHD of skin, gastrointestinal tract, or cGVHD of lungs.…”
Section: Imatinibmentioning
confidence: 92%
“…1 Alone, trisomy 8 does not appear to be sufficient for leukemogenesis but may be associated with an increased risk of myeloid malignancy. 1 To investigate further the contribution of þ 8 to AML, we determined the gene expression signature associated specifically with this numerical chromosomal abnormality using large, previously reported, AML microarray data sets 2,3 and data sets derived from AML cell lines. We have identified a novel association between HOXA gene upregulation and þ 8 AML providing new insight into the potential contribution of þ 8 to AML pathogenesis.…”
Section: Conlfict Of Interestmentioning
confidence: 99%
“…1,2 On the other hand, imatinib, a potent tyrosine kinase inhibitor, is known to inhibit the activation of those pathways, 3 and has been investigated for the treatment for steroid-refractory skin cGVHD. 4,5 Although these studies showed that imatinib was effective as salvage treatment for refractory cGVHD, it remains unknown whether the prophylactic imatinib after SCT affects the incidence and severity of cGVHD.…”
mentioning
confidence: 99%
“…12 The fibrotic change in cGVHD, especially extensive cGVHD, was also associated with the production of autoantibodies against platelet-derived growth factor receptor. 13 Rituximab, which depletes B cells in vivo, was reported to have a preventive and curative potential for GVHD. [14][15][16] However, the optimal strategy for B-cell depletion has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%